2020
DOI: 10.5267/j.uscm.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the application of management accounting in Vietnamese enterprises

Abstract: This paper aims to investigate factors affecting the application of management accounting in Vietnamese enterprises. Quantitative research was conducted and data was collected by sending questionnaires to 120 companies in the manufacturing, trading and service sectors in Vietnam. 6 factors were selected to measure the application of management accounting in enterprises through correlation and regression analysis. The results showed that 5 out of 6 factors positively associated with the level of management acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Past EMA research focuses on relevance of environmental accounting (King and Lenox, 2001; Roos et al , 2020), significance of environmental management systems (Salama, 2005), role of EMA but focused on developed countries as well as nonmanufacturing firms (Le and Nguyen, 2018; Zeng et al , 2020), EMA and cost advantage (Christine et al , 2019; Grekova et al , 2013), green accounting disclosure and corporate social responsibility (Hadj, 2020; Horváthová, 2010; Ingrao et al , 2018), problems and prospects of EMA implementation (Iwata and Okada, 2011), institutional pressures and EMA (Latan et al , 2018; Setthasakko, 2010), environmental management strategy and organizational performance (Omran et al , 2021; Rao and Holt, 2005), green production and FP (Chiou et al , 2011; Huang and Li, 2017), barriers to the development of EMA (Setthasakko, 2010; Solovida and Latan, 2017), green environment system and EP (Mansoor et al , 2021; Meacham et al , 2013), management support and EMA (Singh et al , 2019; Yang Spencer et al , 2013), meta-analysis on EP and FP (Le et al , 2019; Sari et al , 2020) and environmental strategy and EP (Christine et al , 2019; Chuang and Huang, 2018).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Past EMA research focuses on relevance of environmental accounting (King and Lenox, 2001; Roos et al , 2020), significance of environmental management systems (Salama, 2005), role of EMA but focused on developed countries as well as nonmanufacturing firms (Le and Nguyen, 2018; Zeng et al , 2020), EMA and cost advantage (Christine et al , 2019; Grekova et al , 2013), green accounting disclosure and corporate social responsibility (Hadj, 2020; Horváthová, 2010; Ingrao et al , 2018), problems and prospects of EMA implementation (Iwata and Okada, 2011), institutional pressures and EMA (Latan et al , 2018; Setthasakko, 2010), environmental management strategy and organizational performance (Omran et al , 2021; Rao and Holt, 2005), green production and FP (Chiou et al , 2011; Huang and Li, 2017), barriers to the development of EMA (Setthasakko, 2010; Solovida and Latan, 2017), green environment system and EP (Mansoor et al , 2021; Meacham et al , 2013), management support and EMA (Singh et al , 2019; Yang Spencer et al , 2013), meta-analysis on EP and FP (Le et al , 2019; Sari et al , 2020) and environmental strategy and EP (Christine et al , 2019; Chuang and Huang, 2018).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Pencatatan dan pelaporan akuntansi yang berbasis aplikasi dilakukan dengan berbagai alasan seperti diantaranya yaitu meningkatkan kualitas layanan publik, menciptakan sistem yang menghemat waktu dan biaya dan menghasilkan laporan yang lebih terstandarisasi (Altin & Yilmaz, 2022). Selain itu pelaporan berbasis aplikasi akan lebih mudah dalam menghasilk an informasi keuangan yang koheren, komparatif dan verifiable (Bui et al, 2020;Le et al, 2020).…”
Section: Pendahuluanunclassified
“…Based on 109 respondents, the results showed that the factors of finance, customers, internal process, and learning and development all have a positive impact on the application of balanced scorecard. The result is the scientific basis for Vietnamese enterprises to have a succesful application of balanced scorecard to improve their performanc Le, Bui, Tran and Nguyen (2019) conducted a study of 120 Vietnamese enterprises in the fields of production, trade and services to identify factors affecting management accounting applications of enterprises in this field. The results showed that five out of six factors affecting management accounting application include enterprise size, organizational culture, organizational structure, technology, and human resources.…”
Section: Management Accounting Applications In Vietnammentioning
confidence: 99%
“…The result indicated that the perceived benefits have the most influence on online trust of Vietnamese customers. Le et al (2019) did the research to identify the main factors affecting customers' decision to use mobile banking service in Vietnam by using TAM and UTAUT models. The research indicated the perceived ease-of-use, and perceived trust affecting the intention to use mobile banking in Thanh Hoa province of Vietnam.…”
Section: The Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%